Ficcionalização e autoficcionalização "em alguma parte alguma": do processo maquínico de construção e desconstrução de si na poesia de Ferreira Gullar - Tavares, Felipe de Almeida (2014)
The purpose of this study is to develop the concept of autofictionalization of the subject in Ferreira Gullar’s poetry. Since this concept was not found in any text studied in the literature review, we hold our beliefs in Gilles Delleuze’s and Felix Guattari’s principles about the corporeal and incorporeal, and their pure transformation. Starting from the idea that the phrase autofictionalization is deverbative, i.e. a noun that comes from a verb - fictionalize – it is possible to understand that, as a verbal phenomenon from the act of writing, the subject created through autofictionalization will merely have a surface effect, i.e. an effect made possible by language, more specifically, by the verbal action present in the act of writing. Thus, an author would only need writing in first person, so that, consciously or not, this effect would be produced. Our understanding of autofictionalization – the surface effects – differs from the idea of autofiction, since, unlike the latter, it does not imply a cause and effect relationship and takes place regardless the author’s will.